Meta-analysis of the effects of overexpression of WRKY transcription factors on plant responses to drought stress - Yuan Guo (BMC Genetics, 2019)
Abstract Background The tryptophan-arginine-lysine-tyrosine (WRKY) transcription factors play important roles in plants, allowing them to adapt to environmental conditions that are not normally conducive to plant growth; in particular, drought. There has been extensive research on WRKY transcription factors and the effects of their overexpression in plants on resistance to drought stress. However, due to the materials (the type and species of donor and receptor, promoters) and treatments (the type and time of stress) used, different and often confounding results have been obtained between studies. Meta-analysis is a powerful statistical tool that can be used to summarize results from numerous independent experiments on the same research topic while accounting for variability across experiments. Results We carried out a meta-analysis of 16 measured parameters that affect drought resistance in plants overexpressing WRKY transcription factors and wild-type plants. We found that only one of these parameters was significantly different between transgenic and wild-type plants under drought and control conditions at a 95% confidence interval (p = 0.000, p = 0.009, respectively). Eleven of the sixteen parameters were obviously different in WRKY transgenic plants under drought and control conditions (SV, p = 0.023, SSC, p = 0.000, SOD, p = 0.012, SFW, p = 0.000, RL, p = 0.016, Pro, p = 0.000, POD, p = 0.027, MDA, p = 0.000, H2O2, p = 0.003, EL, p = 0.000, CHC, p = 0.000, respectively), seven of the eleven obviously different parameters showed positive effect (SSC, SOD, Pro, POD, MDA, H2O2, EL), four of them revealed negative effect (SV, SFW, RL, CHC). Conclusion We have found that only one of these parameters was significantly different between transgenic and wild-type plants under drought and control conditions respectively, at a 95% confidence interval. And eleven of sixteen parameters showed obviously different of WRKY-overexpressed plants under different conditions (water-stressed and normal), suggesting that WRKY transcription factors play an important role in plant responses to drought stress. These findings also provide a theoretical basis for further study of the role of WRKY transcription factors in the regulation of plant responses to environmental stress.